2014
DOI: 10.1111/hpb.12192
|View full text |Cite
|
Sign up to set email alerts
|

Live liver donors’ risk thresholds: risking a life to save a life

Abstract: Potential donors were risk takers and were willing to donate when given the opportunity. They accepted significant risks, especially if they had a close emotional relationship with the recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 123 publications
(200 reference statements)
0
17
0
3
Order By: Relevance
“…Third, uncertainty surrounding wait‐list time can make it difficult to plan other aspects of one's life such as travel . And finally, greater understanding about wait‐list time may impact medical decision‐making such as the role and benefit for living donation . Given these uncertainties, some limited evidence exists that stress in the pretransplant period can be reduced through increased education and preparation about what to expect in this phase of care, although the ability to reduce stress has not been consistently demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…Third, uncertainty surrounding wait‐list time can make it difficult to plan other aspects of one's life such as travel . And finally, greater understanding about wait‐list time may impact medical decision‐making such as the role and benefit for living donation . Given these uncertainties, some limited evidence exists that stress in the pretransplant period can be reduced through increased education and preparation about what to expect in this phase of care, although the ability to reduce stress has not been consistently demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…3-10 but studies on stem cell transplant 11,12 liver transplant 8,13 and lung transplant14 were also included. No studies focused on uncertainty of family members.…”
Section: Resultsmentioning
confidence: 99%
“…25 Additionally, studies have reported that risk information is “not important in their decision [to donate]” 4 because they wished to save the recipient's life. 13,26 Although the sample was too small for sub-analyses, the donor's relationship to the recipient may have played a role in donors minimizing risks. A factor contributing to this pattern of ignoring “routine” risks was donors' expressed familiarity with surgical risks.…”
Section: Discussionmentioning
confidence: 99%